1993
DOI: 10.1029/93gl00091
|View full text |Cite
|
Sign up to set email alerts
|

OH(ν,N) column densities from high‐resolution Earthlimb spectra

Abstract: Individual OH(ν,N) rotational state population column densities have been derived from spectral analysis of CIRRIS 1A nighttime earthlimb airglow data. Both pure rotation and vibration‐rotation fundamental spectra have been examined, providing unique information on highly excited rotational states of OH(ν=0‐6). The relative populations of the four spin sublevels have also been determined. These findings provide important insights into OH dynamics at the mesopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The accurate determination of tangent heights is crucial in the case of OH emission at the mesopause, since the radiance occurs over such a small altitude range. As discussed previously Dodd et al, 1993a], the observed OH(v,N) line intensities are very sensitive to the interferometer viewing angle. At the 100-km tangent height a change in pitch angle of 10 mrad (0.6 ø) results in a tangent height change of 15 km, providing a very sensitive means of discriminating against the possible effects of shuttle-induced radiance.…”
Section: Tangent Height Determinationmentioning
confidence: 65%
“…The accurate determination of tangent heights is crucial in the case of OH emission at the mesopause, since the radiance occurs over such a small altitude range. As discussed previously Dodd et al, 1993a], the observed OH(v,N) line intensities are very sensitive to the interferometer viewing angle. At the 100-km tangent height a change in pitch angle of 10 mrad (0.6 ø) results in a tangent height change of 15 km, providing a very sensitive means of discriminating against the possible effects of shuttle-induced radiance.…”
Section: Tangent Height Determinationmentioning
confidence: 65%
“…For the case of OH, a 200 K rotational distribution only approximates the actual population distribution in the lower rotational levels [ Cosby and Slanger , 2006]; however, this approximation is sufficiently accurate for confident identification of the OH lines. As noted by Pendleton et al [1989] and by Dodd et al [1993], the population distribution in higher rotational levels of OH ( J ′ ≥ 7.5) is much hotter. We follow the population distributions given by Cosby and Slanger [2006] to model these high levels for the identifications.…”
Section: Identification Proceduresmentioning
confidence: 77%
“…cm -1 region for a tangent height of 85 km, the spectrum obtained as the average of three spectra with similar tangent heights and emission intensities. Spectra such as that shown in Figure 1 were fit using methods described in a previous publication [Dodd et al, 1993]. Observed radiance was found to be closely reproduced at all tangent heights by including six molecular bands: the 03 vl+v 3 (band origin 2111 cm 'l) and vl+v:+v3-v: (2084 cm 'l) combination bands, the OH 9-8 band (2236 cm-1), and the 1-0 bands of nClaO (2143 cm-1), 13ClaO (2096 cm-1), and nC180 (2092 cm'l).…”
Section: Subtraction Of Modeled 03 Oh and 12c160 (Main Isotope) Radmentioning
confidence: 99%
“…We have previously reported a preliminary analysis of high-altitude earthlimb emission spectra from the CIRRIS 1A experiment in the 4.7 •m region [Dodd et al, 1993].…”
Section: Introductionmentioning
confidence: 99%